IDENTIFICATION THE CATCH AND FRESHNESS LEVEL OF KM SARI USAHA 09 IN BITUNG - Hutapea, Roma Yuli; Achmad, Asyarul; Pramesthy, Tyas Dita (Aurelia Journal, 2025)
Catch handling is a series of activities or treatments for fish without changing the basic structure and shape of the fish itself. Currently, the best handling is the application of a cold chain, which is to keep the fish cold (low temperature). The principle of proper handling of catches, namely, (3C+1Q) consists of cold, clean, careful, and quick. This study aimed to identify the catch of KM Sari Usaha 09 and to identify the organoleptic results of the catch on KM Sari Usaha 09 while on board and on land. The study was conducted from January to May 2023. Data collection methods were observation, documentation, and interviews. Data analysis was descriptive, and organoleptic tests were conducted on the main and by-catch fish. The handling of the catch on KM Sari Usaha 09 has an Organoleptic Test value when on board with a value of 9 for eyes (very fresh), 8.9 for gills (very fresh), 8.7 for meat (very fresh) and 8.8 for texture (very fresh), while the results on land are 6.6 for eyes (fresh), 6.8 for gills (fresh), 6.7 for meat (fresh) and 6.9 for texture (fresh).